Implementation of Digital Marketing Strategy in MSME Development in Candisari Ungaran Village - Rachmawati, Meida; Widagdo, Teguh Harso; Sudiyono, Sudiyono; Nurcahyo, Satria Avianda; Ali, Ahmad (CV. Publikasi Indonesia, 2023)
Candisari Village is a village where some of its MSMEs have utilized digital marketing platforms. With the rapid development of technology, the digital world and the internet have also impacted the field of marketing. The marketing trend, which was initially conventional (offline), has now shifted to digital (online). This study adopts a qualitative approach and descriptive analysis approach, which means using a qualitative approach to understand and describe the implications of analysis principles contained in MSMEs' digital marketing strategies. The research aims to gather information about digital marketing strategies for the development of micro, small, and medium-sized enterprises (MSMEs). The digital marketing strategies implemented by food and beverage MSMEs in Candisari Village include marketing through social media platforms and various e-commerce applications such as GrabFood, GoFood, and ShopeeFood. To promote their businesses, the majority of MSMEs utilize Instagram, Facebook, TikTok, and WhatsApp as platforms to upload attractive photos and videos of their products on their Instagram accounts, including Instagram Reels, Instagram Feed, and Instagram Stories. Overall, MSMEs in Candisari Village have experienced progress and healthy competition in business development after implementing digital marketing strategies, leading to the advancement of their businesses